Mechanisms of antimicrobial-induced nephrotoxicity in children. (1st August 2019) - Downes, Kevin J; Hayes, Molly; Fitzgerald, Julie C; Pais, Gwendolyn M; Liu, Jiajun; Zane, Nicole R; Goldstein, Stuart L; Scheetz, Marc H; Zuppa, Athena F
Abstract: Drug-induced nephrotoxicity is responsible for 20% to 60% of cases of acute kidney injury in hospitalized patients and is associated with increased morbidity and mortality in both children and adults. Antimicrobials are one of the most common classes of medications prescribed globally and also among the most common causes of nephrotoxicity. A broad range of antimicrobial agents have been associated with nephrotoxicity, but the features of kidney injury vary based on the agent, its mechanism of injury and the site of toxicity within the kidney. Distinguishing nephrotoxicity caused by an antimicrobial agent from other potential inciting factors is important to facilitate both early recognition of drug toxicity and prompt cessation of an offending drug, as well as to avoid unnecessary discontinuation of an innocuous therapy. This review will detail the different types of antimicrobial-induced nephrotoxicity: acute tubular necrosis, acute interstitial nephritis and obstructive nephropathy. It will also describe the mechanism of injury caused by specific antimicrobial agents and classes (vancomycin, aminoglycosides, polymyxins, antivirals, amphotericin B), highlight the toxicodynamics of these drugs and provide guidance on administration or monitoring practices that can mitigate toxicity, when known. Particular attention will be paid to paediatric patients, when applicable, in whom nephrotoxin exposure is an often-underappreciated cause of kidney injury.